PEMBUKTIAN TERBALIK DALAM PERKARA TINDAK PIDANA KORUPSI (Analisis Putusan PN.TIPIKOR Samarinda NO.11/PID.SUSTPK/2016/PN.SMR) - Yulian Yusuf, Niken; Kurniawati, Wa Ode Intan; Ningsih, Risky Sri Wahyu (Jurnal Multidisipliner Bharasumba, 2023)
This study aims to determine the extent to which the defendant's right to prove reversed against the charges of the public prosecutor in the Corruption Crime Decision Number: 11/Pid.Sus.TPK/2016/PN.Smr. and to find out about the legal considerations of the Panel of Judges in the Samarinda Corruption Court decision No.11 /Pid.Sus. TPK/2016/PN.Smr.. The results of this study indicate that 1. The factor that can free the Defendant from all charges of the Public Prosecutor in the Corruption Crime case is the emergence of new evidence submitted in reverse by the Defendant in front of the trial which then becomes a comparison of the quality of the assessment of evidence between the evidence submitted by the Public Prosecutor and the evidence submitted by the Defendant through his Legal Advisor, the evidence submitted by the Public Prosecutor sourced from the results of the police investigation related to letter evidence that requires testing by an expert has been refuted according to the facts revealed in the trial, namely: a. The factor of the existence of letter evidence submitted by the Defendant in the case of Corruption Crimes. The factor of the existence of letter evidence submitted by the Defendant in front of the trial, regarding the Geotehnik Study of Runway Improvement Development (Repair of Runway Land Phase I - 75,000 m2 in 2010) by Gadjah Mada University in March 2016. bThe factor of testing evidence from, Report on the Results of Expert Activities of Borneo University Tarakan, Faculty of Engineering No. 022/UN51.3/TU/2015 dated March 6, 2015 Regarding : The defendant's right to reverse proof, in accordance with the provisions of Article 37 paragraph (1) of Law No.31 of 1999 on the Eradication of Corruption, as amended by Law No.20 of 2001 on amendments to Law No.31 of 1999 on the Eradication of Corruption, states "The defendant has the right to prove that he did not commit the crime of corruption", the defendant has submitted evidence of letters, photographs and witnesses A Decharge and experts, as well as the facts revealed at trial.